Study of the stress of the tensor tympani muscle for different cases of the eardrum. - Garbe, Carolina (2019)
The middle ear contains tree ossicles: malleus, incus and stapes. The movement of the ossiscles can be enhanced by two muscles, the muscle of the stapes (stapedius muscle) and the muscle of the malleus (tensor tympani).